Janka Hescheles’ 'Locomotive' (to Bełżec) - Morawiec, Arkadiusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
This article concerns the influence of the most famous Polish poem for children: Lokomotywa by Julian Tuwim, particularly in three “Holocaust” paraphrases of this work, written by children in the ghetto and the concentration camps – the poems Lokomotywa by Jerzy Ogórek, Pociągu świst by Jerzy Orłowski, and especially Bełżec by Janka Hescheles.